User experience in mobile application design: utility defined context of use - Lubis, Muharman; Sutoyo, Edi; Azuddin, Muna; Handayani, Dini (IOP Publishing, 2019)
Mobile application has been offered tremendous benefit to the user in providing solution especially related to accessibility and availability. Product functions are important but with the better user experiences, it will have more advantages, which somehow increase its level adoption and retention within context. User experience (UX) is the outcome that this study want to achieve through implementing user centred design in the process by defining the set of methods and phases, which are loosely connected each other to solve the problem arisen. This study identified the lack of integration process within driving communities to have service in motorcycle driving practice, permission letter and rental.